Formulasi Sediaan Lulur Body Scrub Pelembab Kulit Ekstrak Daun Kedondong (Spondias dulcis) - Cucu Arum Dwi Cahya; Andy Febriady; Sri Rezeki Anggriani (Jurnal Indah Sains dan Klinis, 2024)
Background: Body scrub is a skincare preparation that effectively removes dead skin cells caused by free radicals. Kedondong leaves are a plant with extraordinary wealth, especially its vitamins, namely A, B1, and C, and have a high antioxidant content, so they can be used as a natural moisturizer for the skin. Objective: This research aims to formulate a body scrub containing Kedondong leaf extract. Method: Kedondong leaf extract was formulated with a concentration of 10.0; 15.0; and 20.0%. Evaluation of the body scrub formulation includes organoleptic, homogeneity, pH, irritation and moisture using a skin analysis tool. Results: Research shows that the body scrub formulation with Kedondong leaf extract is homogeneous and has a shape, colour and pH value corresponding to skin pH standards. This formulation also does not irritate and provides adequate moisture for the skin. The formulation with a concentration of 20% (F4) shows the best effectiveness, being able to moisturize the skin up to 47.8%. Conclusion: Kedondong leaves can be formulated into an effective body scrub to improve the condition of dull skin to make it brighter, cleaner and smoother.